Vanadium Toxicity in Mice: Possible Impairment of Lipid Metabolism and Mucosal Epithelial Cell Necrosis in the Small Intestine. (August 2013) - Imura, Hitomi; Shimada, Akinori; Naota, Misaki; Morita, Takehito; Togawa, Masako; Hasegawa, Tatsuya; Seko, Yoshiyuki
Because precise information as to the toxicity of vanadium is required for practical use of vanadium compounds as antidiabetic drugs, we examined vanadium toxicity in mice fed normal diet or high-fat diet (C57BL/6N, male, 7 weeks) by oral administration of ammonium metavanadate (AMV) with a maximum dose of 20 mgV/kg/day. Marked lipid accumulation in hepatocytes, renal epithelial cells, and mucosal epithelial cells of the small and large intestines and severe degeneration, necrosis, and loss of mucosal epithelial cells in the small intestine were observed. These pathological changes were more severe in mice fed high-fat diet than mice fed normal diet, and the intensity of the changes increased with increase in the administered dose of AMV. By electron microscopy, the number and size of lipid droplets in hepatocytes were increased. In the small intestine, a TUNEL assay showed a decreased number of positive cells, and positive cells for acrolein immunohistochemistry were observed specifically in the mucosal epithelial cells indicating degeneration and necrosis in the AMV-treated group, suggesting that a possible factor responsible for cell necrosis in the small intestine could be oxidative stress. In conclusion, AMV may impair cellular lipid metabolism, resulting in lipid accumulation, and induce mucosal epithelial cell necrosis in the small intestine.